Local development from a basin perspective: case of the Zaña valley basin - Vergara Campos, Carlos Miguel (2022)
Local development from a basin perspective: the case of the Zaña valley basin” aims to describe the implementation of policies in the management of local development in the districts located in the Zaña valley basin. The central problem of our research is Is there in the local development management in the districts located in the Zaña Valley Basin a basin conception that is based on the rational use of natural resources, the development of social capital with identity and the sustainability of the environment? The object of study are the 8 districts that are located within the Zaña valley basin. It was determined that in the management of local development in the districts of the Zaña valley basin there is no basin approach. The public policies of the central government, regional and local governments are centralist and limit the spaces for participation of social actors. The need arises to incorporate a vision of account in the conception, design and implementation of public policies that values the concept of sustainability of natural resources and generates spaces and efficient mechanisms for the participation of the population.